Pengaruh Pengendalian Internal dan Penerapan Akuntansi Terhadap Kualitas Laporan Keuangan pada Kantor Kepala Desa Sionggoton Kec.Simangambat Kab. Padang Lawas Utara. - Perjuangan Siregar; Marliyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the influence of internal control and the application of accounting in the office of the Sionggoton village head. This research uses quantitative methods, data collection techniques by distributing questionnaires and the sample in this research was 30 people in the office of the Sionggoton village head using a saturated sampling technique. The results of the research show that internal control and the application of accounting have a positive and significant effect on the quality of financial reports, namely that there is a positive influence of internal control on the quality of financial reports in the office of the Sionggoton village head; The quality of financial reports at the Sionggoton village head's office is positively influenced by the application of accounting; The quality of financial reports at the Sionggoton village head's office is influenced positively and significantly by the application of accounting principles and internal control.